Clinicopathologic and molecular characterization of myeloid neoplasms with isolated t(6;9)(p23;q34). (20th March 2017) - Visconte, V.; Shetty, S.; Przychodzen, B.; Hirsch, C.; Bodo, J.; Maciejewski, J. P.; Hsi, E. D.; Rogers, H. J.
Summary: Introduction: The t(6;9)(p23;q34);DEK‐NUP214 [t(6;9)] abnormality is found in 0.7–1.8% of patients with acute myeloid leukemia (AML) or myelodysplastic syndromes (MDS). FLT3‐ ITD mutations are detected in t(6;9) patients. The t(6;9) abnormality is associated with poor outcomes. We studied the clinicopathologic and molecular profiles of patients with AML/MDS carrying t(6;9). Methods: We collected clinical data of nine patients with AML/MDS with isolated t(6;9) (median age = 41 years; male/female = 4/5) and genotyped DNAs using whole exome, Sanger, and targeted sequencing. Results: Our cohort was characterized by frequent multilineage dysplasia (56%), absence of phospho‐STAT3/STAT5 expression, presence of myeloid markers (CD13, CD33, CD34, CD117, HLA‐DR) with an aberrant expression of CD7, and poor outcome (median survival of 20 months). Although basophilia has been described in association with t(6;9), we observed lack of marrow basophilia in our cohort. Molecularly, 83% (5/6) of patients with AML/MDS with t(6;9) were characterized by at least one somatic mutation. Among them, four patients showed multiple mutations. FLT3‐ ITD mutations were detected in 33% of patients (2/6); 80% (4/5) of mutant patients died even after hematopoietic stem cell transplantation. Conclusion: Our data demonstrated that AML/MDS patients with t(6;9) have diverse molecular mutations regardless of the presence of FLT 3 mutations, which may contribute to their poor survival outcomes.